(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article explores the traditional manifestations of freedom and enlightenment ideas in the history of Turkic literary development. The authors analyze the literary heritage of various historical periods of Turkic peoples to reveal the origins, evolution, and artistic expression of these ideas. Special attention is given to themes such as free thinking, personal liberty, social justice, and spiritual elevation that are evident in works of literature. Additionally, issues related to connections with world literature are also discussed throughout the articles.